Simultaneous osteosarcoma and adenocarcinoma of the gallbladder: A rare case report and literature review - Cho, Jin-Kyu; Lee, Woohyung; Jang, Jae Yool; Yang, Jung-Wook; Hong, Soon-Chan; Jeong, Chi-Young (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Cho JK, Lee W, Jang JY, Yang JW, Hong SC, Jeong CH. Simultaneous osteosarcoma and adenocarcinoma of the gallbladder: A rare case report and literature review. Turk J Gastroenterol 2019; 30(6): 569-72